2019
DOI: 10.1111/ggi.13712
|View full text |Cite
|
Sign up to set email alerts
|

Reference range of clinical blood tests in physically independent patients of advanced age with groin hernia in a Japanese hospital

Abstract: Aim The present study was carried out to determine the reference ranges of 43 frequently used blood tests in daily practice for physically independent patients of advanced age. Methods We identified all patients aged ≥20 years who underwent groin hernia repair at Itoigawa General Hospital in Niigata, Japan. The patients’ characteristics, preoperative data and prescribed medications were obtained by reviewing the electronic medical records. Results Of 284 patients, 266 with independence in activities of daily l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
1
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
1
1
2
Order By: Relevance
“…Additionally, the characteristics of our patients may differ from those of Japanese adults in the general population. The incidence of diabetes in our study population was higher than expected (29) , possibly because the surgical indications included vitrectomy for diabetic retinopathy. Notably, substantial numbers of patients with psychosis, dementia, and intellectual disability that were included in this survey possibly due to general anesthesia is selected for adults who are unable to remain immobile during eye surgery.…”
Section: Discussioncontrasting
confidence: 48%
“…Additionally, the characteristics of our patients may differ from those of Japanese adults in the general population. The incidence of diabetes in our study population was higher than expected (29) , possibly because the surgical indications included vitrectomy for diabetic retinopathy. Notably, substantial numbers of patients with psychosis, dementia, and intellectual disability that were included in this survey possibly due to general anesthesia is selected for adults who are unable to remain immobile during eye surgery.…”
Section: Discussioncontrasting
confidence: 48%
“…Because distigmine is mainly eliminated by renal excretion [32], the relative decrease in distigmine clearance might have been associated with her distigmine overdose. Our previous study showed an age-dependent decline in serum ChE levels in physically independent adults [33]. As shown in Table 2, a marked decrease in ChE activity was observed in all cases in which the serum ChE was measured.…”
Section: Discussionmentioning
confidence: 62%
“…sürelerinin uzaması yaşlılık tanımlamalarını da değiştirmiş ve Dünya Sağlık Örgütü'ne (DSÖ) göre yaşlılık üç alt gruba ayrılarak 65-74 yaş arası erken yaşlılık, 75-84 yaş arası yaşlılık, 85 yaş ve üzeri ise ileri yaşlılık olarak tanımlanmıştır (2). 65 yaş ve üzeri hasta popülasyonunda hem yaşa bağlı karın duvarındaki destek dokusunun zayıflaması hem de eşlik eden komorbid durumlardan dolayı artan karın içi basınca bağlı olarak inguinal herniler genç nüfusa oranla daha sık görülmektedir (3). Ayrıca 65 yaş ve üzeri hastalarda uygulanan anestezi ve cerrahi işleme bağlı morbidite ve mortalite oranları da artmaktadır (4).…”
Section: Yaşamunclassified
“…Postoperatif dönemde ince barsak rezeksiyonu yapılan 2 ve yapılmayan 1 hasta olmak üzere toplam 3 hastada atelektazi, rezeksiyon yapılan ve Mc Vay onarım yapılan 2 hastada ise yara yeri enfeksiyonu gelişti. Hastaların ortalama hastanede kalış süreleri 8,21±3,78(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) gündü. Postoperatif 3 hastada mortalite görüldü.…”
unclassified